Knowledge of HIV and/or AIDS and HIV testing services among young men in South Africa - Ndlovu, Sithembiso M. S.; Ross, Andrew; Ndirangu, James (African journal of primary health care & family medicine, 2023)
BackgroundThe youth is at a heightened risk of immunodeficiency virus and/or acquired immunodeficiency syndrome (HIV and/or AIDS) infection because of risk-taking behaviour. There remains a gap in understanding young men’s knowledge of HIV and/or AIDS and HIV testing services (HTS) in hard-to-reach communities in South Africa.AimThis article aimed to explore young men’s knowledge of HIV and/or AIDS, including HTS in Ladysmith, KwaZulu-Natal (KZN).SettingRural and peri-urban areas around the town of Ladysmith.MethodsEmploying a qualitative descriptive research design, 17 young men aged between 18 and 30 years were purposively and conveniently sampled and interviewed using WhatsApp and landline audio calls to collect their data, which was thematically analysed.ResultsYoung men had good knowledge of HIV and/or AIDS but lacked knowledge about HTS and HIV self-testing (HIVST). They obtained their information about HIV and/or AIDS and HTS from various sources and were aware of where to access HTS. They were generally unaware and supportive of HIVST.ConclusionMale-targeted HIV and/or AIDS knowledge and testing interventions are needed to encourage and support young men to test for HIV. Human immunodeficiency virus self-testing should be explored as an alternative to clinic-based service to encourage young men to know their status, specifically those with limited access to or are reluctant to attend clinics. Strengthening HIV and/or AIDS education could facilitate better decision-making towards HIV testing among young men.ContributionThis study contributes to an understanding of young adult men’s knowledge of HIV and/or AIDS and HTS in underserved settings in South Africa.